1971
DOI: 10.1049/piee.1971.0028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rotor eccentricity on acoustic noise from induction machines

Abstract: The variations of acoustic-noise power radiated from electric machines, having varying degrees of eccentricity of the rotor in the stator bore, were studied using a specially constructed rig in an anechoic chamber. A series of noise components, which were found in expsriments to vary considerably with rotor eccentricity, were identified analytically from the expressions for the mode numbers and frequencies of the magneticforce waves, taking into account the stator and rotor slotting, eccentricity and iron satu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 3 publications
0
21
0
1
Order By: Relevance
“…基本理論が検討され (Ellison and Yang, 1971) ,それらが体系的にまとめられた (Yang, 1981 Fig. 2 Configuration of the experimental apparatus.…”
Section: 実現するためにも非常に重要な技術と考えられる.近年は静粛な環境でモータを使用することも多いため,騒音 低減に対する要求はunclassified
“…基本理論が検討され (Ellison and Yang, 1971) ,それらが体系的にまとめられた (Yang, 1981 Fig. 2 Configuration of the experimental apparatus.…”
Section: 実現するためにも非常に重要な技術と考えられる.近年は静粛な環境でモータを使用することも多いため,騒音 低減に対する要求はunclassified
“…Noise monitoring is carried out by measuring and analyzing the acoustic noise spectrum. In [16], Ellison and Yang carried out tests in an anechoic chamber. It was found that slot harmonics in the acoustic noise spectra from an induction motor were functions of static eccentricity.…”
Section: A Condition Monitoring Techniques Reviewmentioning
confidence: 99%
“…Consider the first-order permeance equation due to stator-rotor slotting, given by (3). The effective permeance wave is obtained by taking into account the mutuals by the multiplication procedure and can be written as …”
Section: B Field Harmonics Due To Slottingmentioning
confidence: 99%
“…Also, there is a trend to use these results in the designing of online monitoring of motors in industrial plants. A considerable amount of detailed information on the airgap harmonics of three-phase induction motors is available in the literature [1]- [3]. On the contrary, the available papers on the single-phase motors is rather limited.…”
Section: Introductionmentioning
confidence: 99%